Navigating the tensions between ethics and effectiveness in development communications and marketing. Issue 2 (17th February 2022) - Cameron, John David; Kwiecien, Olivia
ABSTRACT: This paper examines the ways that communications and marketing professionals with international development non-governmental organisations (NGOs) understand and navigate the tensions between ethical and effective communications about global poverty and development. The paper is based on interviews with 16 senior communications officers in Canadian NGOs and with six marketing firms that support the non-profit sector. The paper finds that most of the communications professionals we interviewed did not view their work from an ethical perspective. Based on these findings, the paper argues that a renewed debate about the ethical dimensions of representing global development and poverty is urgently needed.